Toward a choreography of congregating: A practice-based perspective on organizational absorptive capacity in a semiconductor industry consortium. Issue 4 (September 2014) - Müller-Seitz, Gordon; Güttel, Wolfgang
Previous studies on absorptive capacity focus either upon dyadic interorganizational constellations or upon an organization's environment in general, thus neglecting other managerially relevant interorganizational constellations. Furthermore, despite significant advancements in our understanding, we still know little about the way absorptive capacity actually unfolds on an organizational level, as many studies predominantly take absorptive capacity as a quantitatively measurable phenomenon. We address these two shortcomings by following recent calls for a practice perspective on absorptive capacity. In particular, we reveal the choreography of knowledge absorption practices in an interorganizational network. Based on an empirical study in the semiconductor industry, we put forward the thesis that this can be achieved by congregating, that is, repeatedly exchanging face-to-face ideas at network-wide venues such as conferences or workshops. We illustrate how a lead firm in this industry carefully choreographs congregating, which helps the organization acquire knowledge from network partners and utilize the knowledge internally. Herein, we contribute a practice perspective on how to influence organizational absorptive capacity when engaging with an interorganizational network as a distinctive organizational form. A practice lens also entails being sensitive to the political dimension of absorptive capacity. Moreover, choreographies of bundles of absorptive capacity-relevant practices represent a concept to inform future research.